2003
DOI: 10.1182/blood-2002-06-1837
|View full text |Cite
|
Sign up to set email alerts
|

CD44-stimulated human B cells express transcripts specifically involved in immunomodulation and inflammation as analyzed by DNA microarrays

Abstract: A number of studies have implicated a role for the cell surface glycoprotein CD44 in several biologic events, such as lymphopoiesis, homing, lymphocyte activation, and apoptosis. We have earlier reported that signaling via CD44 on naive B cells in addition to B-cell receptor (BCR) and CD40 engagement generated a germinal center-like phenotype. To further characterize the global role of CD44 in B differentiation, we examined the expression profile of human B cells cultured in vitro in the presence or absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…During the germinal center reaction, however, CD44 is downregulated (Dahlenborg et al, 1997;Feuillard et al, 1995;Kremmidiotis and Zola, 1995). CD44 ligation by anti-CD44 in human B cells also results in upregulation of the genes for IL-6, IL-1a, and b 2 -adrenergic receptor (b 2 -AR)-indicating a role in immunomodulation and inflammation (Hogerkorp et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During the germinal center reaction, however, CD44 is downregulated (Dahlenborg et al, 1997;Feuillard et al, 1995;Kremmidiotis and Zola, 1995). CD44 ligation by anti-CD44 in human B cells also results in upregulation of the genes for IL-6, IL-1a, and b 2 -adrenergic receptor (b 2 -AR)-indicating a role in immunomodulation and inflammation (Hogerkorp et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte homeostasis can control the balance between an insufficient number of cells to mount an immune response or the excessive proliferation and/or overstimulation of an immune response associated with pathological conditions, such as cancer and autoimmune disorders (16,42). Studies using antibodies to block CD44 function have demonstrated a role in lymphocyte activation, differentiation, homing/migration, and proliferation (15,21,31,44,47). We have shown that CD44 expression is diminished in the Ets1 ⌬VII mutants.…”
Section: Thymomegaly In Ets1mentioning
confidence: 99%
“…P2RY1 is a member of a family of G-protein-coupled receptors that are expressed on monocytes and macrophages and are involved in inflammatory and immunity pathways [20]. MLLT3 is known to regulate erythrocyte and megakaryocyte differentiation [21], and is also induced by ligation of CD44, a cell surface receptor for hyaluronan (HA) the concentration of which is increased in inflammatory and immune responses, and which also binds to LYVE-1 [22]. Mutation of the MLLT3 gene has also been linked to a patient with neuromotor development delay, cerebellar ataxia and epilepsy [23].…”
Section: Discussionmentioning
confidence: 99%